An Arabic letter by Charles Huber in the Ottoman archives | خطاب عربي لشارل هوبر في الأرشيف العثماني - Suhail | سهيل, Saban | صابان (King Fahad National Library | مكتبة الملك فهد الوطنية, 2024)
The researcher found an Arabic letter among thousands of Arabic letters found in the Ottoman archives in Istanbul. This letter is preserved in the Y.PRK.UM classification. Under the number 6/100 from the aforementioned archive of the French doctor and traveler Charles Huber (), who spoke in his memoirs translated into Arabic entitled “A Journey in the Central Arabian Peninsula” about the same topic that he recorded in his speech. The agreement between the information contained in the documents of the Ottoman archive and the book in which It was written by Hooper completely...and this indicates the credibility of both of them and their authenticity in their rare information | عثر الباحث على خطاب عربي ضمن آلاف الخطابات العربية الموجودة في الأرشيف العثماني بإستانبول .. وهذا الخطاب المحفوظ في تصنيف Y.PRK.UM. تحت الرقم 6/100 من الأرشيف المذكور للطبيب والرحالة الفرنسي شارل هوبر( ) الذي تحدث في مذكراته المترجمة إلى اللغة العربية بعنوان "رحلة في الجزيرة العربية الوسطى" عن الموضوع ذاته الذي دوَّنه في خطابه، فالتوافق بين المعلومات الواردة في وثائق الأرشيف العثماني وبين الكتاب الذي ألفه هوبر تام .. وهذا يدل على مصداقية كل منهما وصحتهما في معلوماتهما النادرة